Traveling history of the Armenian four gospels dated to 1686 (NCM RAR 82) - Khatuna Gaprindashvili (Banber Arevelagitut'yan Instituti)
The colophons of the old manuscripts, in general, convey important information about various persons, noble families, churches, monasteries, historical facts or contemporary political situations. In addition, the colophons often allow us to trace the history of creation, composition, purpose, preservation and sometimes to follow the journey of the manuscripts. One of such books is the Old Printed Armenian Four Gospels (RAR 82) preserved in the Rare Books Room at K. Kekelidze Georgian National Centre of Manuscripts.